UPLC-HRMS Analysis Revealed the Differential Accumulation of Antioxidant and Anti-Aging Lignans and Neolignans in In Vitro Cultures of Linum usitatissimum L - Bose, Shankhamala; Munsch, Thibaut; Lanoue, Arnaud; Garros, Laurine; Tungmunnithum, Duangjai; Messaili, Souhila; Destandau, Emilie; Billet, Kévin; St-Pierre, Benoit; Clastre, Marc; Abbasi, Bilal Haider; Hano, Christophe; et al. (Frontiers in Plant Science, 2020)
The application of plant tissue culture in cosmetics is gaining a new impetus in the last few decades and it is anticipated that the cosmetic industries in the coming years will rise to an annual turnover of a few hundred billion US dollars. Here, we focused on Linum usitatissimum (L.) a well-known plant for its potent cosmetic properties. Following their establishments from 3 distinct initial explant origins (root, hypocotyl and cotyledon) and the selection of optimal hormonal concentrations, 2 in vitro systems (callus vs cell suspensions) were subjected to different light conditions. In-depth phytochemical analysis by UPLC-HRMS not only confirmed the high (neo)lignans accumulation capacity of this species, but also enriched it with 7 newly described (neo)lignans. Ten-point over 30 days for growth kinetics and variation in phytochemical composition for the 2 different in vitro systems cultivated under light or dark conditions were evaluated and revealed strong variations. The antioxidant (i.e. four different in vitro assays based on hydrogen-atom transfer or electron transfer mechanism) and anti-aging (i.e. four in vitro inhibition potential of the skin remodeling enzymes: elastase, hyaluronidase, collagenase and tyrosinase) were evaluated. A prominent hydrogen-atom transfer antioxidant mechanism was evidenced by the DPPH and ABTS assays. Potent tyrosinase and elastase inhibitory activities were also observed and was strongly influenced by the in vitro system and light conditions, thus, correlation analysis through principal component analysis correlated some (neo)lignans with these biological activities. Altogether these results confirmed and enriched the interest for cosmetic applications of flax (neo)lignans accumulated in different in vitro systems subjected to distinct light conditions and revealed the importance of the optimization of these parameters for specific applications.